Effective cross hedging: evidence from physical crude palm oil and its inter-related agricultural futures contracts / Noryati Ahmad ... [et al.] - Ahmad, Noryati; Zainudin, Ahmad Danial; Abdul Rahim, Fahmi; Ho, Catherine S F (Universiti Teknologi MARA Cawangan Selangor, 2018)
Since its establishment, Crude Palm Oil futures contract (FCPO) has been used to directly hedge its physical crude palm oil (CPO). However, due to the excessive speculation activities on crude palm oil futures market, it has been said to be no longer an effective hedging tool to mitigate the price risk of its underlying physical market. This triggers the need for market players to find possible alternatives to ensure that the hedging role can be executed effectively. Thus this investigation attempts to examine whether other inter-related grains and oil seed futures contracts could serve as effective cross-hedging mechanisms for the CPO. Weekly data of inter-related futures contracts from Chicago Board of Trade (CBOT) and Dalian Commodity Exchange (DCE) are employed to cross hedge the physical crude palm oil prices. The study starts from 2006 until 2016. Empirical results indicate that FCPO is still the best futures contract for hedging purposes while Chicago Soybean (CBOTBO) provides second best alternative if cross-hedging is considered.